PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING BERBANTUAN MIND MAP DALAM MEREMEDIASI MISKONSEPSI GETARAN - Lastriana, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The aims of this study is to determine the effect of the application Student Facilitator and Explaining (SFE) learning model aided  mind map to remediate students’ misconceptions on the vibration topic in SMA Mujahidin Pontianak. This reaserch formed as Pre-Experimental design involving 23 students’ as the study sample were selected by intact group random sampling. The method used instrument is 10 multiple choice questions with 3 alternative answers with an open reasoning. Based on the results showed misconception profile of learners before and after remediation implemented. Based on the analysis, the highest misconceptions on pre-test  is 97% and the post-test is 60%. Average reduction for each student misconceptions is 39% and the average decrease misconceptions about each indicator was 38%. Based on calculations by Mc Nemar test, overall there has been a change misconceptions learners fairly significant with an average percentage of 39% (medium category). Keywords: Remediation, Misconceptions, SFE